The Use of HIV Pre- and Postexposure Prophylaxis Among a Web-Based Sample of HIV-Negative and Unknown Status Cisgender and Transgender Sexual Minority Men: Cross-sectional Study - Steven A John; K Marie Sizemore; Ruben H Jimenez; S Scott Jones; Andrew E Petroll; H Jonathon Rendina (JMIR Publications, 2022)
BackgroundHIV disproportionately affects sexual minority men (SMM) in the United States. ObjectiveWe sought to determine past HIV postexposure prophylaxis (PEP) use and current and prior pre-exposure prophylaxis (PrEP) use among a web-based sample of cisgender and transgender men who have sex with men. MethodsIn 2019, HIV-negative and unknown status SMM (n=63,015) were recruited via geosocial networking apps, social media, and other web-based venues to participate in a brief eligibility screening survey. Individuals were asked about past PEP use and current and prior PrEP use. We examined associations of demographics, socioeconomic indicators, and recent club drug use with PEP and PrEP use, as well as the association between past PEP use and current and prior PrEP use using generalized linear models and multinomial logistic regression. Statistical significance was considered at P<.001, given the large sample size; 99.9% CIs are reported. ResultsPrior PEP use was reported by 11.28% (7108/63,015) of the participants, with current or prior PrEP use reported by 21.95% (13,832/63,015) and 8.12% (5118/63,015), respectively. Nearly half (3268/7108, 46%) of the past PEP users were current PrEP users, and another 39.9% (2836/7108) of the participants who reported past PEP use also reported prior PrEP use. In multivariable analysis, past PEP use was associated with current (relative risk ratio [RRR] 23.53, 99.9% CI 14.03-39.46) and prior PrEP use (RRR 52.14, 99.9% CI 29.39-92.50). Compared with White men, Black men had higher prevalence of past PEP use and current PrEP use, Latino men had higher prevalence of PEP use but no significant difference in PrEP use, and those identifying as another race or ethnicity reported higher prevalence of past PEP use and lower current PrEP use. Past PEP use and current PrEP use were highest in the Northeast, with participants in the Midwest and South reporting significantly lower PEP and PrEP use. A significant interaction of Black race by past PEP use with current PrEP use was found (RRR 0.57, 99.9% CI 0.37-0.87), indicating that Black men who previously used PEP were less likely to report current PrEP use. Participants who reported recent club drug use were significantly more likely to report past PEP use and current or prior PrEP use than those without recent club drug use. ConclusionsPrEP use continues to be the predominant HIV prevention strategy for SMM compared with PEP use. Higher rates of past PEP use and current PrEP use among Black SMM are noteworthy, given the disproportionate burden of HIV. Nonetheless, understanding why Black men who previously used PEP are less likely to report current PrEP use is an important avenue for future research.